3DSHAPE-AR: PROFIL PENALARAN SPASIAL MATEMATIS MAHASISWA DI POLITEKNIK MELALUI PEMBELAJARAN GEOMETRI BERBASIS AUGMENTED REALITY [3DSHAPE-AR: PROFILE OF STUDENTS' MATHEMATICAL SPATIAL REASONING AT POLYTECHNICS THROUGH GEOMETRY LEARNING BASED ON AUGMENTED REALITY] - Pratiwi, Indah Riezky; Afriansyah, Riki; Andriyanto, Shidiq; Erianti, Agnes; Julianti, Rima (Universitas Pelita Harapan, 2025)
Students' low mathematical reasoning skills affect their academic achievement in various fields. The field of Engineering is a domain that requires good mastery of geometric concepts, especially at the Polytechnic. However, in reality, students' mastery of Geometry concepts is still very low. This is because students' mathematical spatial reasoning skills are less honed. One of the contributing factors is that the learning resources used are still focused on books which do not support students to be more able to manipulate spatial representations in memory and mentally, so the 3DShape-AR application was developed. This research was conducted to see the mathematical spatial reasoning profile of students at the Polytechnic before and after studying using the 3DShape-AR application. This research was carried out qualitatively using a descriptive method by selecting 2 student answers using purposive sampling which then examined and described the profile of students' mathematical reasoning skills before and after learning using the 3DShape-AR application. From the analysis stage, it was concluded that the use of the 3DShape-AR application in geometry learning was able to provide changes in the quality of students' mental rotation, spatial orientation and spatial visualization components. These three components are components that describe the quality of a person's mathematical reasoning skills. The advantage of using the 3DShape-AR application is that students can explore various spatial shapes by rotating single or combined spatial shapes in various degrees to see the real visualization of the spatial shapes. Interesting content like this allows students to imagine space from various perspectives and then this understanding can be used to solve problems. It is also able to help students store visual patterns in their memory, carry out mental transformations, and manipulate internal representations. BAHASA INDONESIA ABSTRACT: Rendahnya keterampilan penalaran matematis mahasiswa mempengaruhi prestasi akademik mereka di berbagai bidang. Bidang Teknik merupakan salah satu ranah yang memerlukan penguasaan konsep geometri yang baik terutama di Politeknik. Namun kenyataannya penguasaan konsep Geometri mahasiswa masih sangat rendah. Hal ini disebabkan karena keterampilan penalaran spasial matematis mahasiswa yang kurang terasah. Salah satu faktor penyebabnya adalah karena sumber belajar yang digunakan masih terpusat pada buku yang kurang mendukung mahasiswa untuk dapat lebih mampu memanipulasi representasi bangun ruang di dalam memori dan mental sehingga dikembangkanlah aplikasi 3DShape-AR. Penelitian ini dilakukan untuk melihat bagaimana profil penalaran spasial matematis mahasiswa di Politeknik sebelum dan setelah belajar menggunakan aplikasi 3DShape-AR. Penelitian ini dilaksanakan secara kualitatif dengan metode deskriptif dengan memilih 2 jawaban mahasiswa secara purposive sampling yang kemudian menelaah dan mendeskripsikan profil keterampilan penalaran matematis mahasiswa sebelum dan sesudah belajar menggunakan aplikasi 3DShape-AR. Dari tahap analisis diperoleh Kesimpulan bahwa penggunaan aplikasi 3DShape-AR dalam pembelajaran geometri mampu memberikan perubahan kualitas komponen rotasi mental, orientasi spasial dan visualisasi spasial mahasiswa. Ketiga komponen ini merupakan komponen yang menggambarkan bagaimana kualitas keterampilan penalaran matematis seseorang. Keunggulan dari penggunaan aplikasi 3DShape-AR adalah mahasiswa bisa mengeksplorasi berbagai bentuk bangun ruang dengan merotasi bangun ruang tunggal maupun kombinasi ke berbagai arah derajat untuk melihat bentuk visualisasi real dari bangun ruang tersebut. Konten menarik seperti ini membuat mahasiswa dapat membayangkan bangun ruang di berbagai perspektif untuk selanjutnya, pemahaman ini dapat digunakan untuk memecahkan masalah. Hal ini juga mampu membantu mahasiswa dalam menyimpan pola visual dalam memori mereka, melakukan transformasi mental, dan memanipulasi representasi internal.